2014
DOI: 10.1155/2014/573825
|View full text |Cite
|
Sign up to set email alerts
|

IL-17-Expressing CD4+and CD8+T Lymphocytes in Human Toxoplasmosis

Abstract: This study aimed to measure the synthesis of Th1 and Th2 cytokines by mononuclear cells after culture with live T. gondii and identified Th17 (CD4+) and Tc17 (CD8+) cells in toxoplasma-seronegative and toxoplasma-seropositive parturient and nonpregnant women. Cytometric bead arrays were used to measure cytokine levels (IL-2, TNF-α, IFN-γ, IL-4, IL-5, and IL-10); immunophenotyping was used to characterize Th17 and Tc17 cells, and the cells were stained with antibodies against CD4+ and CD8+ T cells expressing IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
0
19
1
Order By: Relevance
“…It is important to consider that IL-17 is a classic example of a “double-edged sword” that is capable of inducing a protective immune response to pathogen infection, while also having the ability to contribute to autoimmune disorders (Curtis and Way, 2009 ; Korn et al, 2009 ). IL-17-expressing CD4+ and CD8+ T-lymphocytes play significant roles in the inflammatory response to Toxoplasma gondii and Trypanosoma cruzi , thus blocking parasite invasion or replication in humans (Miyazaki et al, 2010 ; Silva et al, 2014 ). The importance of Th17 cells was demonstrated in their ability to control the development of such intracellular protozoa and promote the differentiation of activated macrophages and neutrophils, thereby supporting the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider that IL-17 is a classic example of a “double-edged sword” that is capable of inducing a protective immune response to pathogen infection, while also having the ability to contribute to autoimmune disorders (Curtis and Way, 2009 ; Korn et al, 2009 ). IL-17-expressing CD4+ and CD8+ T-lymphocytes play significant roles in the inflammatory response to Toxoplasma gondii and Trypanosoma cruzi , thus blocking parasite invasion or replication in humans (Miyazaki et al, 2010 ; Silva et al, 2014 ). The importance of Th17 cells was demonstrated in their ability to control the development of such intracellular protozoa and promote the differentiation of activated macrophages and neutrophils, thereby supporting the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…An unexpected observation in our mouse vaccination studies was the induction of a substantial subset of CD8 T cells staining positive for IL-17. These have occasionally been observed in various fungal and protozoan disease states ( 40 42 ) and were found in one study within tuberculosis-induced pleural infusions ( 43 ). As yet, it is unclear whether their presence is beneficial.…”
Section: Discussionmentioning
confidence: 80%
“…Interleukin-17A plays a key role in anti-microbial and anti-fungal defence by inducing cytokines, chemokines that affect neutrophil activation [ 36 , 37 ]. Some studies have demonstrated that IL-17 cells mediate host defences against Chagas disease, mucocutaneous leishmaniasis, alveolar disease and opportunistic infections such as pneumocystosis, toxoplasmosis and cryptosporidiosis [ 38 42 ]. IL-17 is also involved in the pathogenesis of autoimmune diseases and transplant rejection reactions of organs [ 37 ].…”
Section: Discussionmentioning
confidence: 99%